Pengaruh Keberadaan Material Butir Pasir terhadap Sifat Mekanik Timbunan pada Studi Kasus Disposal Pit SJS PT Bukit Asam (Persero) Tbk Unit Pertambangan Tanjung Enim - Muhammad Qistan Hafits; Eddy Ibrahim; Taufik Toha (Dinasti Research, 2026)
Embankment slope stability is a critical challenge in open-pit coal mining operations, particularly within the Tanjung Enim Mining Unit (UPTE) of PT Bukit Asam Tbk. This study investigates the influence of varying clay and sand compositions on the physical and mechanical properties of embankment geomaterials to determine the optimal configuration for operational stability. An experimental research design was conducted using material samples from Pit SJS, involving five composition variations: 100% clay; 75% clay – 25% sand; 50% clay – 50% sand; 25% clay – 75% sand; and 100% sand. Geotechnical parameters were evaluated through Standard Proctor compaction tests and Direct Shear tests to determine maximum dry density, optimum moisture content, bearing capacity, cohesion, and internal friction angle. The results demonstrate that both maximum dry density and bearing capacity exhibit an increasing trend as sand content rises, reaching peak values at the 50% clay – 50% sand composition before declining at higher sand ratios. Conversely, optimum moisture content significantly decreases as sand content increases. Shear strength analysis reveals that cohesion reaches its maximum at the 50/50 ratio, while pure sand (100% sand) exhibits significant